Characterization and Mutational Analysis of a Monogalactosyldiacylglycerol Synthase Gene OsMGD2 in Rice - Basnet, Rasbin; Zhang, Jiarun; Hussain, Nazim; Shu, Qingyao (Frontiers in Plant Science, 2019)
Monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol (DGDG) are the two predominant galactolipids present in the photosynthetic membrane in many photosynthetic organisms, including algae and higher plants. These galactolipids are the main constituents of thylakoid membrane and are essential for chloroplast biogenesis and photoautotrophic growth. In silico analysis revealed that rice (Oryza sativa L.) genome has three genes encoding MGDG synthase (OsMGD1, 2, and 3). Although subcellular localization analysis demonstrated that OsMGD2 is localized to chloroplast, its expression was observed mainly in anther and endosperm, suggesting that MGDG might have an important role in the development of flower and grain in rice. Knock-out mutants of OsMGD2 were generated employing the CRISPR/Cas9 system and their morphology, yield and grain quality related traits were studied. The leaf of osmgd2 mutants showed reduced MGDG (∼11.6%) and DGDG (∼9.5%) content with chlorophyll a content decreased by ∼23%, consequently affecting the photosynthesis. The mutants also exhibited poor agronomic performance with plant height and panicle length decreased by ∼12.2 and ∼7.3%, respectively. Similarly, the number of filled grains per panicle was reduced by 43.8%, while the 1000 grain weight was increased by ∼6.3% in the mutants. The milled rice of mutants also had altered pasting properties and decreased linoleic acid content (∼26.6%). Put together, the present study demonstrated that OsMGD2 is the predominantly expressed gene encoding MGDG synthase in anther and grain and plays important roles in plant growth and development, as well as in grain quality.